Wireless Sensor Networks in oil and gas industry: Recent advances, taxonomy, requirements, and open challenges. (1st July 2018) - Aalsalem, Mohammed Y.; Khan, Wazir Zada; Gharibi, Wajeb; Khan, Muhammad Khurram; Arshad, Quratulain
Abstract: The industrial world of oil and gas involves critical processes and machinery for the exploration, extraction, refining, transporting and marketing petroleum products. Oil and gas companies need to control, monitor, maintain and secure the processes and industrial assets in an efficient manner. To resolve the critical challenges of pipeline condition, corrosion and integrity monitoring, gas leak detection, and other related problems, Wireless Sensor Networks (WSN) provide promising solutions. WSN is the most prevalent technology used in oil and gas industry that has provided remote facilities to detect and report the anomalous events like the positions of leakage, corrosion or any other damage. A few existing studies in the literature do not cover the recent WSN based systems and techniques and only review the pipeline monitoring systems. These surveys lack the recent WSN based systems developed for monitoring and detecting damages to pipelines as well as other assets of oil and gas industry. In this paper we present a comprehensive review and detailed comparison of the most recent systems or techniques developed for monitoring various anomalous events that are involved in the three sectors (upstream, midstream, downstream) of oil and gas industry. We also describe the important requirements of WSNs to be deployed in the oil and gas industry. Finally, we highlight critical challenges of oil and gas industry.